Commercial Discrimination as Religious Messaging in 303 Creative v. Elenis - Satta, Mark (Religions, 2024)
In 303 Creative LLC v. Elenis, a web designer sought a legal right to refuse to make wedding websites for same-sex couples while making wedding websites for other couples as a service provided by her business open to the public. The web designer also sought a legal right to post a notice on her business webpage stating that she would refuse to provide such services for same-sex couples’ weddings. Here, I argue that 303 Creative marks a fairly radical break from previous legal cases dealing with whether service providers have the legal right to deny services for same-sex weddings. This is because, if we take the web designer at her word, the web designer appears to have sought these legal rights, in significant part, in order to use an act of commercial discrimination as an act of religious message sending. In support of this conclusion, I argue that acts of selective commercial service constitute the primary means by which the web designer sought to promote her preferred religious messages and that these acts of selective commercial service are acts of discrimination. I also discuss some of the significance of this case for religion and politics in the United States.